2022
DOI: 10.1186/s12894-021-00951-z
|View full text |Cite
|
Sign up to set email alerts
|

Urinary manifestations in African American and Caucasian inflammatory bowel disease patients: a retrospective cohort study

Abstract: Background Inflammatory bowel diseases (IBD), like ulcerative colitis (UC) and Crohn’s disease (CD), are associated with urinary extra-intestinal manifestations, like urolithiasis and uncomplicated urinary tract infections (UTIs). The literature reviewed for this study identifies an increased association of CD and urolithiasis against the general population as well as UC. Furthermore, the rates in which urinary comorbidities manifest have not been well characterized in cross-race analyses. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Thus, medical orders and self-medication use of antibiotics to treat UTIs are mostly observed in sexually active individuals, which resulted in recurrent infection and the development of drug-resistant clones [30]. The current study showed that most patients belong to the age group 16-50 (including male and female), similar nding has been reported in South Africa [31] and even in America [32]. However, in contrast to our study, Canadian data revealed an increase in UTI among older patients [33].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, medical orders and self-medication use of antibiotics to treat UTIs are mostly observed in sexually active individuals, which resulted in recurrent infection and the development of drug-resistant clones [30]. The current study showed that most patients belong to the age group 16-50 (including male and female), similar nding has been reported in South Africa [31] and even in America [32]. However, in contrast to our study, Canadian data revealed an increase in UTI among older patients [33].…”
Section: Discussionsupporting
confidence: 79%
“…We have linked S. aureus to UTI in males reported rst time but a high prevalence of S. aureus UTI in females has been reported previously [37]. In contrast, some reports mentioned that Escherichia coli is the key causative agent in UTI, reports from another part of the Democratic Republic of Congo as well as USA, Africa and Ethiopia but our study mentioned the second most important bacteria is Escherichia coli about 12% [20,32,38]. In our study second most, important bacteria are Escherichia coli followed by the Stepatocuccus spp, Klebsiella spp., Bacillus spp., Edwardsiella spp., Leclercia spp., Pneumatera spp., Budvicia spp., Cedecea spp.…”
Section: Discussionsupporting
confidence: 37%
“…Moreover, IBD patients with anorectal complications, which include perianal abscesses and anal fistulas, appear to have an increased risk for UTIs. It could be explained that in these patients anorectal complications could lead to bacterial translocation from the perineum to the bladder ( 53 , 54 ). Accordingly, the overgrowth of E. coli strains with extraintestinal virulence capacity in IBD patients could act as a risk factor for UTI development.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding CD, the prevalence of urolithiasis was 7.1%, 95% CI (3.6%-13.6%), nephrolithiasis 4.6%, 95% CI (3.6%-5.8%), and both 11.9%, 95% CI (8.4%-16.6%). Based on [29,33,35,36,38,39] showed that there was a significant association between developing urolithiasis and the disease duration of IBD (OR = 1.03, 95% CI: 3.…”
Section: Prevalence Of Renal Stones In Ibd Patientsmentioning
confidence: 99%